Hadrosaurs from Cañada Ancha (Cerro del Pueblo Formation; upper Campanian-?lower Maastrichtian), Coahuila, northeastern Mexico - Rybakiewicz, Sandra; Stinnesbeck, Wolfgang (Cretaceous research, 2019)
At Cañada Ancha, about 15 km northwest of Saltillo, northeastern Mexico, deposits of the upper Campanian-?lower Maastrichtian Cerro del Pueblo Formation exhibit bone clusters of disarticulated hadrosaurids, tentatively assigned here based on maxillary features to Velafrons coahuilensis and a second yet undetermined taxon. We discuss the taphonomy of the material as transported and buried on a delta plain. Orientation and breakage of bones as well as absence of strong abrasion indicate short-distance and high-energy transport by a viscose ‘flash flood’ or debris flow.